Spectral Characteristics of Fluctuating Aerodynamic Forces Acting on Rectangular Prisms - Jiadong Zeng; Zhitian Zhang; Mingshui Li; Shaopeng Li (Applied Sciences, 2023)
The present work is devoted to the role of boundary layer turbulence on the spectral characteristics of fluctuating wind loads on large aspect-ratio rectangular prisms. Seven rectangular rigid models with different side ratios (1/4~4) were created, and simultaneous pressure experiments were conducted under the boundary layer turbulence flows. Using the measured data, the power spectrums of the fluctuating aerodynamic forces were calculated, and then, the spectral characteristics under different turbulent boundary layer flows were analyzed. In contrast to the typical power spectrum model, the main factors affecting the spectral characteristics of the fluctuating aerodynamic loads are presented and discussed in this study. The power spectrum of the rectangular prism was significantly impacted by the turbulent wind field, primarily because higher turbulence intensity levels result in a lower spectral peak and a wider spectral bandwidth, which also redistributes spectral energy. In particular, the effect on the spectral properties of across-wind fluctuating loads was stronger, and the turbulent disturbance modified the lateral separation flow structure, causing the reattachment phenomenon to occur earlier on rectangular prisms with small side ratios, which effectively altered the spectral properties. Thus, a normalized across-wind fluctuating wind load spectrum model is proposed, taking into account the effects of incoming turbulence, the side ratio, vortex shedding, separation reattachment flow-induced spectral bandwidth changes, and high-frequency fluctuations.